Comparison of the Accuracy of Hexagon Imaging Software versus Digital and Hand Tracings of Lateral Cephalograms - Alzamili, Hayder; Tehranchi, Azita; Namdari, Mahshid; Kavousinejad, Shahab (Journal of Dental School, 2021)
Objectives The aim of this study was to evaluate the validity and reliability of a newly designed cephalometric analysis program (Hexagon software) in comparison with manual and digital (Dolphin software) tracings. Methods Pre-treatment lateral cephalometric radiographs of 32 adult patients between 18 to 41 years (10 males and 22 females, mean age of 22.78 ± 5.17 years) were randomly chosen. For each radiograph, 10 angular and 6 linear measurements were calculated using three different methods (manual and digital using two different software programs). The cephalograms were manually traced using acetate paper, x-ray light box, 0.3 mm HB pencil, ruler, and protractor. For digital tracing, cephalograms were traced with Dolphin vertion-10 (USA) and Hexagon (Iran) software programs. All the analyses were performed by one operator 2 times with at least a four-week interval between the two tracings. The intra-class correlation coefficient (ICC) was used to evaluate the intra-examiner agreement, while the differences between the methods were analyzed using paired t-test, and ANOVA. Results The intra-examiner repeatability of all measurements in all three tracing methods showed high agreement. Differences in measurements between the two software programs and hand tracing were not statistically significant for any of the cephalometric parameters (P>0.05). Conclusion The results demonstrated that the accuracy of cephalometric tracing by the Hexagon software was similar to the Dolphin software, and the manual tracing technique.